DEVELOPMENT AND VALIDATION OF ENGLISH LEARNING MATERIAL USING FLIP PDF PROFESSIONAL FOR JUNIOR HIGH SCHOOL STUDENTS - Amaliah R. Nggilu; Marilou D. Tino; Bambang Widi Pratolo (PROJECT (Professional Journal of English Education), 2024)
Most teachers often use textbook as a primary resource book for ideas and instructional activities as well as giving guides for what they do. This research is focus on developing English learning material using flip PDF professional in Writing skill for Grade VII in SMP N 1 Tapa based on curriculum in Indonesia. The aims of this research were: (1) To investigate the difficulties of SMP N 1 Tapa Grade VII students in writing composition, (2) To find out the supplemental tool that can be developed to address the difficulties by the students, (3) To develop appropriate English learning materials using flip PDF professional for Grade VII students in SMP N 1 Tapa. This research is one of the processes to develop new products or improve existing products. The product that will be produce from this research is an e-book to develop junior high school students' writing skills in English learning for class VII. The researchers used ADDIE development model in making the product. The writer's developed instructional material can serve as supplementary resources for classroom teaching and learning. This implies that the materials existing in the textbook can still be utilized.